Bill Cosby, the Lustful Disposition Exception, and the Doctrine of Chances - Wesley M. Oliver (Washington University Law Review, 2016)
On December 30, 2015, an affidavit of probable cause alleged that William H. Cosby, Jr., Ed.D., a comedian whose storied career spanned decades, committed aggravated indecent sexual assault upon Andrea Constand. For decades, women have been coming forward claiming to have been the victims of Cosby’s unwanted sexual advances, most of them claiming that Cosby drugged them and took advantage of them when they were in an unconscious state. Despite the number of accusers over decades, thus far only one criminal count has been announced. At this point, it appears that the statute of limitation would preclude an indictment charging any criminal acts against the other alleged victims. That does not mean that we have heard the last of the other accusers. Even though evidence of a defendant’s bad character is “not admissible for the purpose of proving the person acted in conformity therewith,” common sense would dictate that a trier of fact should hear from the other victims who claim Cosby similarly assaulted them. What are the odds that one man could be falsely accused by fifty women? A few courts have asked exactly this question using something called the doctrine of chances, a rule that expressly considers the likelihood that the defendant is innocent of the present offense in light of what we know about his past. Rather than conducting such an analysis, however, a number of courts tend to merely admit all prior sexual misconduct under what is known as the lustful disposition exception. Prior sexual misconduct, however, is no more likely than other types of bad acts to predict future misconduct. Because courts more readily admit prior acts to predict future conduct when the acts are of a sexual nature, it seems likely that Cosby’s other accusers will be allowed to testify. The result in this case seems correct, but the logic is certainly questionable.
Keywords: Criminal Law; Evidence; Bill Cosby; Lustful disposition exception; Doctrine of chances; Sexual assault; Character evidence; Prior sexual misconduct